Strategies of Supporting Progressed Learners for Quality Teaching and Learning in Vhembe District, Limpopo, South Africa - Fhulufhelo Patrick Muedi; Azwidohwi Philip Kutame; Thelma Ngidi; Chinaza Uleanya (JETL (Journal of Education, Teaching and Learning), 2021)
Progressed learners differ from their counterparts. The difference is reflected in their assimilation, retention and abilities to reproduce what they are taught. Meanwhile, progressing learners due to policy is insufficient, certain support strategies are to be in place. Hence, the study investigated the strategies of supporting “qualified to be progressed” (QP) learners for quality learning and teaching. Mixed methods was employed for data collection. Random and purposive sampling techniques were used to select teachers and School Management Team (SMT) members respectively who formed the study sample. The study was conducted in 10 purposively selected secondary schools in the Vhembe education, Limpopo, South Africa. Questionnaires were used to collect data from 165 selected teachers who were the respondents for the quantitative part of the study. Meanwhile interviews were conducted for the 10 SMTs who formed the participants for the qualitative part of the study. Percentage was used to analyse the quantitative data, while the qualitative data were used for triangulation. The finding of the study showed amongst others that there are no specific support strategies put in place to assist progressed learners to catch up with their counterparts. The study recommends that schools and relevant education stakeholders put in place support strategies to assist progressed learners.